A longitudinal VBM study monitoring treatment with erythropoietin in patients with Friedreich ataxia. Issue 4 (12th May 2014) - Santner, Wolfram; Schocke, Michael; Boesch, Sylvia; Nachbauer, Wolfgang; Egger, Karl
Background: Recombinant human erythropoietin (rhuEPO) has received considerable attention because of its neuroprotective properties. It has recently been reported that rhuEPO increases frataxin levels in combination with clinical improvement in rhuEPO treated patients with Friedreich ataxia (FRDA). Purpose: To determine possible therapy dependent intracranial volume changes after treatment with rhuEPO using voxel-based morphometry (VBM). Material and Methods: Nine FRDA patients were scanned on the same 1.5-Tesla MRI scanner before and after treatment with rhuEPO. FRDA patients received 5000 IU rhuEPO thrice weekly subcutaneously for a time period of 8 weeks followed by 2000 IU thrice weekly over 6 months. To test for re-test reliability a control group of 12 healthy volunteers were scanned twice on the same scanner without rhuEPO treatment. Neurological state was defined by the Friedreich Ataxia Rating Scale (FARS) and the Scale for the Assessment and Rating of Ataxia (SARA). Statistical parametric mapping software was used for image processing and statistical analysis. Results: When comparing follow-up scans after rhuEPO treatment with baseline scans ( P <0.001 uncorrected) an increase of gray matter volume was observed bilaterally in the Pulvinar and the posterior parietal cortex. Moreover, clinical improvement detected using specific Ataxia scores correlated with VBM results in the pulvinar. Conclusion: Given the limitation of a small sample size, our study confirms previous findings that MRI may serve as reliable biomarker in neurodegenerative diseases as well as in monitoring of microstructural changes representing disease progression and/or therapy effects.